The management of head and neck tumors with high technology radiation therapy. Issue 1 (2nd January 2016) - Mendez, Lucas Castro; Moraes, Fabio Ynoe; Poon, Ian; Marta, Gustavo Nader
Abstract : Squamous cell carcinoma is responsible for 90% of the head and neck cancers affecting over 600, 000 people worldwide. Radiation therapy, surgery and chemotherapy are the most important treatment modalities in head and neck squamous cell carcinoma. The aim of this review is to summarize the recent innovations in head and neck radiation therapy, which intends to appreciate the cutting-edge intensity-modulated radiation therapy strategies to mitigate long-term toxicities and evaluate promising technologies in the field as adaptive treatment, dose painting and proton therapy.